Efektivitas Pelaksanaan Kegiatan Kampung Binaan Keluarga Sakinah Di Kabupaten Siak - Riyaldi, Rino; Al Mansur, Muhammad (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2024)
The Sakinah family development carried out by the Siak Regency Government through the Sakinah Family Development Village activity aims to create a religious society and the economic prosperity of families in Siak Regency. Various activities have been carried out in KBKS. Activities that started from the trial period (2012-2014) have been running for 10 years so far, and the effectiveness needs to be examined to see whether the program has been effective or not. This research is field research using a qualitative descriptive approach with data collection techniques using observation, interviews and documentation studies. The research results show that the implementation of KBKS activities is considered effective. This is proven based on the results of research in the field which shows that the Sakinah Family Assisted Village (KBKS) activities are running well and optimally, starting from the pilot/launching and socialization stage, the coaching stage, the monitoring/evaluation stage and the post-evaluation stage.